The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.3177/jnsv.45.213
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Sulfur Compounds in Human Expiration after Eating Raw or Heat-Treated arlic.

Abstract: SummaryVolatile sulfur compounds arising from grated raw or heat-treated garlic in both in-vitro and in-vivo tests were gas-chromato graphically analyzed. In in-vitro tests, the head-space vapor gas from garlic in a vial was analyzed. It was clarified that allyl mercaptan arising from raw garlic decreased with the passage of time and other volatile low-molecular sulfur compounds (LMSC) did not show remark able changes. The change of LMSC from heat-treated garlic was also studied. Methyl mercaptan and allyl mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 12 publications
(14 reference statements)
0
18
0
Order By: Relevance
“…Tamaki and Sonoki analyzed volatile sulfur compounds arising from grated raw or heat-treated garlic; it was found that the higher the volatile sulfur compound level, the stronger the garlic flavor or malodor was. Raw garlic showed a strongest smell than heattreated garlic [25].…”
Section: Garlic Odormentioning
confidence: 99%
“…Tamaki and Sonoki analyzed volatile sulfur compounds arising from grated raw or heat-treated garlic; it was found that the higher the volatile sulfur compound level, the stronger the garlic flavor or malodor was. Raw garlic showed a strongest smell than heattreated garlic [25].…”
Section: Garlic Odormentioning
confidence: 99%
“…The strong increase of the concentration of acetone might be indicative of enhanced metabolism of serum cholesterol, triglycerides and total lipids in the bloodstream. Low-molecular sulfur compounds (LMSC), namely, allyl mercaptan, methyl mercaptan and allyl methyl sulfi de, were detected in signifi cant amounts in human breath after garlic ingestion (Tamaki and Sonoki 1999 ). The quantities of these compounds arising from heat-treated garlic were smaller than those from raw garlic.…”
Section: Garlic Breathmentioning
confidence: 98%
“…Allyl methyl sulphide, allyl mercaptan and methyl mercaptan were determined to be the important volatile low-molecular weight sulphur compounds expired. Analytical concentrations for the candidate substance allyl methyl sulphide .096] for raw garlic and heated garlic at the first measurement time point (0 minutes) were about 0.03 ppm and 0.05 ppm, respectively, and after 30 minutes had decreased to approximately 0.01 and <0.05 (Tamaki and Sonoki, 1999). It was determined that the major volatile metabolite detected in breath EFSA Journal 2012; 10(2):2455 and plasma from human subjects which had consumed dehydrated granular garlic and an enteric-coated garlic preparation is allyl methyl sulphide (Rosen et al, 2000;Rosen et al, 2001).…”
Section: ] (Subgroup I)mentioning
confidence: 99%